DEVELOPMENT DEVELOPMENT OF POWERPOINT ASSISTED PUZZLE MEDIA ON FRACTION MATERIALS IN SD: . - Vira Fransiska; Sukmawarti (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2022)
Abstract: This research is motivated by problems in learning Mathematics, namely, the lack of varied and interesting learning media on fractional material. This study aims to design puzzle media with the help of Pointpoints on fractions in elementary school. To find out the feasibility of powerpoint-assisted puzzle media on fractions in elementary school. The method used is Research and Development (RnD) which consists of 5 stages, namely (Analysis, Design, Development, Implementation, and Evaluation). The data collection instrument is a questionnaire. The data obtained in the form of qualitative descriptive analysis data. Based on the analysis of the research data, the results showed that the feasibility level of the learning media developed after validation was declared feasible. The results of the media expert's validation were declared very feasible by obtaining an